Kesantunan Berbahasa dalam Talkshow â€œNeo Democrazyâ€ di Metro TV - Astuti, Rika; R., Syahrul; Ermanto, Ermanto (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purposes of the article were to describe (1 ) good manners principle those are utilized in Talkshow â€œNeo Democrazyâ€ at Metro TV , (2 ) converse strategies those are utilized in Talkshow â€œNeo Democrazyâ€ at Metro TV.Â  This observational data is lingual dialogue record on Talkshow â€œNeo Democrazyâ€ at Metro TV. Gathered data by utilized is tech learn, tech records and tech note. Observational finding can conclude following things. First, good manners principle that is utilized in Talkshow â€œNeo Democrazyâ€ at Metro TV is maksim praise, maksim is humility, maksim is deal, maksim is sympathy, and maksim is generosity. Both of, converse strategy that is utilized in Talkshow â€œNeo Democrazyâ€ at Metro TV is this as follows: frank converse strategy with positive good manners platitude and converse strategy speaks mind with negative good manners platitude. Relevant with research, recommended that maksim maksim's elect good manners gets language in hands down about television used by event filler so discourse it decent so person that is criticized, or is spoken not perceives to be pertained or anger with discourse that announced by comunicator.